To develop of automated vacuum ark unit - Zhukeshov, A.M.; Amrenova, A.U.; Gabdullina, A.T.; Sundetov, T.; Kaibar, A.; Fermakhan, K. (Recent Contributions to Physics, 2014)
The articlediscusses of results of vacuum ark plasma unit work and research. In previous years, the authors have created various vacuum systems, developed a unique technology of pulsed vacuum arc deposition and plasma treatment. These technologies have been tested and have shown high efficiency for hardening of materials and obtaining coatings. However, for implementation in the industry of these technologies need to create a finished product in the form of a technological installation, equipped with an automated control system. The task of creating such system is closely connected with the peculiarities of obtaining and supporting a high vacuum, which requires developers to informed choice of the necessary technical solutions. Features of the proposed development are: Intelligent unit for vacuum control on the basis of the active vacuum gauge and microcomputer compatible with industrial equipment for vacuum systems.